Case report: Magnetic resonance imaging findings of patients with diffuse uterine leiomyomatosis - Zhang, Zanhua; Lin, Xianhui; Wang, Xue; He, Fang; Cai, Weiwei; Min, Xiaoyan; Xiang, Fei (Frontiers in Oncology, 2024)
Background: Diffuse uterine leiomyomatosis (DUL) is a seldom-seen condition, with only a handful of cases of magnetic resonance imaging (MRI) findings documented. In clinical settings, it is often mistaken for multiple uterine leiomyomas due to a lack of adequate recognition of DUL. Objective: This study shows two instances of DUL, underscoring their MRI findings to improve preoperative diagnostic precision. Conclusion: For patients exhibiting multiple uterine leiomyomas with masses present in the parametrial and abdominal cavities, consideration should be given to diagnosing DUL with DPL. The discoveries outlined in this paper furnish insights that can assist in directing treatment choices.